2019
DOI: 10.3390/ijerph16101783
|View full text |Cite
|
Sign up to set email alerts
|

Toward Value-Based Healthcare through Interactive Process Mining in Emergency Rooms: The Stroke Case

Abstract: The application of Value-based Healthcare requires not only the identification of key processes in the clinical domain but also an adequate analysis of the value chain delivered to the patient. Data Science and Big Data approaches are technologies that enable the creation of accurate systems that model reality. However, classical Data Mining techniques are presented by professionals as black boxes. This evokes a lack of trust in those techniques in the medical domain. Process Mining technologies are human-unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 37 publications
(45 reference statements)
0
42
0
Order By: Relevance
“…If both situations, for a p -Value lower than a given threshold, it is concluded that the distributions are significantly different. Following the literature, the threshold was set to 0.05 [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…If both situations, for a p -Value lower than a given threshold, it is concluded that the distributions are significantly different. Following the literature, the threshold was set to 0.05 [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…This technique can be used to highlight the differences with statistical significance between the two models referring to two cohorts. This approach can not only discover when a process is different but also in which parts of the models the differences lie [ 46 ]. Figure 13 and Figure 14 show where processes for adult and young populations differ with respect to the elderly process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, [ 16 ] proposed time-related indicators that focus on the elapsed time between two ER activities, such as triage and doctor seen. In addition to presenting indicators, there have been several applications with the ad-hoc approaches to understand ER processes [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. For example, [ 18 ] introduced an approach to evaluate the capabilities of process mining to the ER process on the stroke case, and [ 19 ] explored the effects of interactive process mining using the value-based technologies.…”
Section: Related Workmentioning
confidence: 99%